ESTIMASI PERHITUNGAN SUMBERDAYA BAUKSIT MENGGUNAKAN LUAS AREA PENGARUH METODE POLIGON PADA BLOK SUNGAI RONGGAS PT KALBAR BUMI PERKASA KECAMATAN TAYAN HILIR KABUPATEN SANGGAU PROVINSI KALIMANTAN BARAT - Dela Kurniasih; Budhi Purwoko; Fitriana Meilasari (JeLAST : Jurnal Teknik Kelautan , PWK , Sipil, dan Tambang, 2022)
Bauxite is the main ore deposit for producing low iron and silica metal aluminum and other clay minerals. PT. Kalbar Bumi Perkasa is a company engaged in bauxite mining and will carry out land acquisition so that it is still in the exploration stage. The purpose of this study was to determine the potential of bauxite resources in the Sungai Ronggas Block at PT Kalbar Bumi Perkasa. The method used to achieve the research objectives is to use the area of influence polygon-incuded method. Determining the area of each block is by determining the limits of the area of influence in each block and then multiplying by the thickness of the bauxite deposit so that the volume of bauxite is obtained, the distribution of bauxite deposits at the study site is determined by a test pit point spacing of 25 meters and a cut off grade of 35%. The result of the research is that the volume of bauxite resources contained in the Sungai Ronggas Block of PT Kalbar Bumi Perkasa is 9,937.50 m3 or equivalent to 15,900.00 tons. Based on COG 35%, bauxite resources are 7,875 m3 or equivalent to 12,600 tons with an average Al2O3 content of 44.98% while bauxite resources <35% are 2,062.5 m3 or equal to 3,300 tons with an average Al2O3 content of 33.42 %.